1998
DOI: 10.1021/jp980855m
|View full text |Cite
|
Sign up to set email alerts
|

The Issue of Morphology and Molecular Accessibility of Swollen Gel-Type Resins:  An Integrated Inverse Steric Exclusion Chromatography−Electron Spin Resonance−NMR Approach

Abstract: A number of microporous fairly hydrophilic poly(N,N-dimethylacrylamide-methylenebisacrylamide) (poly(DMAA-MBAA)) resins (cross-linking degree from 2 to 8%) have been examined with techniques that provide information on the structure on the nanometer scale and molecular accessibility of these materials in the swollen state. Electron spin resonance (ESR), pulsed-gradient-spin-echo nuclear magnetic resonance (PGSE−NMR) spectroscopies, and inverse steric exclusion chromatography (ISEC) gave consistent results in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 18 publications
1
12
0
1
Order By: Relevance
“…It tells us that the spin-probe does reach the nanoporous domains under exploration (i.e., they turn out to be accessible to a molecule of substantial size) and it also inversely qualitatively correlates with the average size of cavities within the investigated swollen polymer framework. [16,18] Typical motionally averaged (t = 10 À11 -10 À9 s) spectra of TEM-PONE inside swollen MASF6 and AAD2 are reported in Figure 7; the situation is qualitatively similar for MASF2, MASF4 and AAD1. Relevant values of t, hyperfine coupling constants (a iso ) and activation energies (E a ) are given in Table 4.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…It tells us that the spin-probe does reach the nanoporous domains under exploration (i.e., they turn out to be accessible to a molecule of substantial size) and it also inversely qualitatively correlates with the average size of cavities within the investigated swollen polymer framework. [16,18] Typical motionally averaged (t = 10 À11 -10 À9 s) spectra of TEM-PONE inside swollen MASF6 and AAD2 are reported in Figure 7; the situation is qualitatively similar for MASF2, MASF4 and AAD1. Relevant values of t, hyperfine coupling constants (a iso ) and activation energies (E a ) are given in Table 4.…”
Section: Introductionmentioning
confidence: 69%
“…[24] Nanometer-level morphology in water-ESR analysis: In previous papers we have extensively shown that the rotational mobility of the spin probe 2,2,6,6-tetramethyl-4-oxo-1-oxypiperidine (TEMPONE) is a good indicator of the molecular accessibility and nanoporosity of swollen gel-type resins that result from the employment of classical bifunctional cross-linking agents. [16][17][18] Good indications of molecular accessibility and nanoporosity were also gathered in the case of macroreticular resins [28] and of the unconventional macro-, meso-and microporous resin polybenzimidazole. [29] When the rotation of TEMPONE is "free", that is, hampered only by moderate microviscosity effects and not by chemisorption phenomena, the fast spin-probe reorientation is able to average out the magnetic anisotropies [30] producing a well-resolved three-line spectrum (Figure 7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pseudo-solution state of a swollen resin particle is highlighted by the relatively high rotational mobility of probe molecules dissolved in the swelling medium (Biffis et al 1995;D'Archivio et al 1998) and by the significant translational mobility possessed by the solvent molecules confined inside the swollen polymer framework as well as by suitable translational probes (Corain et al 2007). For MA materials, a perfectly detectable (scanning electron microscopy) micrometre-level porosity, called macroporosity, is observed already in the dry state (figure 2).…”
Section: (B) Structurementioning
confidence: 99%
“…-developing the application of existing 'analytical' technologies to investigate the nanometre-scale structure of macroreticular and gel-type (GT) CFPs: inverse steric exclusion chromatography, ISEC (Jeȓábek 1985a,b), electron spin resonance (ESR) spectroscopy (Biffis et al 1995), pulse field gradient spin echo NMR (PGSE-NMR) spectroscopy (D'Archivio et al 1998) and cross-polarization magic angle spinning 13 C-NMR (CP-MAS 13 C-NMR) spectroscopy (Pozzar et al 2005); -developing simple synthesis protocols to M 0 /CFP; -controlling the distribution of metal nanoclusters inside the body of resin particles; Burato et al (2009) -exploring the catalytic potency of Pd 0 /CFP in a variety of 'simple' hydrogenation reactions such as cyclohexene hydrogenation (Zecca et al 2000;Centomo et al 2009), chemoselective hydrogenation of 2-ethylanthraquinone to 2-ethylanthrahydroquinone (Biffis et al 2002) and direct synthesis of hydrogen peroxide (Burato et al 2009); -evaluating the possibility of a template effect of the swollen polymer framework on the size of the metal nanoclusters generated in its interior (Corain et al 2004a). …”
Section: Introductionmentioning
confidence: 99%